Reconstruction of Sharia Stock Law in Indonesia: A Normative Analysis of Musharakah Fiqh on the Jakarta Islamic Index - Piryanti, Meri (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2025)
Background. The development of the Islamic capital market in Indonesia has positioned Islamic stocks as a primary investment instrument, normatively constructed based on the musharakah contract. However, the practice of Islamic stocks, represented by the Jakarta Islamic Index (JII), still raises issues regarding their compliance with the substantive principles of fiqh (Islamic jurisprudence) of musharakah, particularly regarding partnership, risk sharing, and fairness. Aim. This study aims to critically analyze the suitability of sharia shares in JII with the principles of fiqh musharakah and to formulate a conceptual reconstruction of sharia shares from the perspective of sharia economic law. Methods. This study uses a normative legal approach with a library research method. The analysis was conducted through a juridical-normative approach to muamalah (Islamic jurisprudence) and a juridical-normative approach by examining fatwas from Dewan Syariah Nasional Majelis Ulama Indonesia (DSN-MUI), Islamic capital market regulations, the Islamic Securities List, and academic literature related to Islamic stocks and musharakah. The data were analyzed qualitatively and descriptively using a critical analysis pattern to compare the principles of musharakah jurisprudence and Islamic stock practices in the Indonesian capital market. Results. Sharia-compliant stocks in the JII have met formal sharia compliance through regulatory screening mechanisms, but do not fully reflect the substantive principles of fiqh of musharakah. Partnership relations, real risk sharing, and the principle of fairness are still diminished due to the dominant capital gain orientation and the transactional nature of share ownership. This study offers a theoretical contribution in the form of a reconstruction of sharia-compliant stocks as partnership-based equity that emphasizes substantive sharia compliance, risk sharing, and a maqasid al-syariah orientation.